RC: The Pied Piper returns - Jenny Jinks (London, Franklin Watts, 2019)
When the Pied Piper returns to Hamlelin, the children are delighted. Their parents have gone safety-mad and banned all sweets, cakes and ice cream too. When the Piper offers to help in return for some of the sweets, Ash, Freddie and Mala agree. But once the parents disappear the children refuse to pay the Piper, and the children soon find life without parents is not so easy